Energy Infrastructure Development Faces Impediments. Issue 9 (April 2015) - Gibbs, Kirstin; Johnson, Tyler; McCarthy, Catherine
<x xml:space="preserve">Abstract</x> While political opposition or regulatory agencies themselves may impede natural gas infrastructure projects, it is often the various environmental and citizen groups protesting these projects that create significant challenges. From the Keystone XL oil pipeline to liquefied natural gas (LNG) export terminals, the strategies for derailing or slowing these projects often depend on the statutory and regulatory tools available, which differ by the governing statute—e.g., the Natural Gas Act (NGA) and the Interstate Commerce Act. Of course, other statutes, such as the National Environmental Policy Act (NEPA), influence how the applicable agency reviews a natural gas infrastructure project.